Long-Term Performance of Radon Barriers in Limiting Radon Flux from Four Uranium Mill Tailings Containment Facilities - Michaud, Alex M. (My University, 2018)
ABSTRACT Compacted clay covers have traditionally been constructed to contain Uranium mill tailings (UMT) at disposal sites throughout the United States. These clay covers, typically referred to as Radon (Rn) barriers, are designed to limit water percolation into and gaseous Radon flux out of Uranium mill tailings piles in accordance with the Uranium Mill Tailings Radiation Control Act of 1978 (UMTRCA), which was enacted to require the safe disposal and long-term containment of Uranium mill tailings. Uranium mill tailings are the by-product of the Uranium mining process and contain low levels of Uranium and its daughters. One of the main requirements stipulated by UMTRCA is to limit the amount of Radon flux from the waste into the atmosphere. Radon (Rn-222), a daughter progeny of Uranium, is a colorless, odorless, radioactive gas (half-life = 3.8 d) that is known to cause lung cancer. UMTRCA requires these barriers to reduce Rn flux emanations from the cover system to a maximum of 20 pCi/m2s (0.74 Bq/m2s). The Rn barriers used at UMTRCA disposal facilities are designed to be a thick, dense, saturated layer with both low permeability and low gaseous diffusivity. The low permeability limits the amount of water flux into the waste from precipitation, while the low gaseous diffusivity allows Radon to attenuate significantly while traveling from the waste towards the surface through the process of diffusion. Because Rn barriers are designed to be very dense and saturated, they create a barrier that is penetrable for Rn, but travel times are very long. Thus, it takes many half-lives for the Rn to travel to the surface, significantly reducing the concentration of the Rn along the way. These Rn barriers are typically covered with one or more protective layers. Many of these Rn barriers were constructed 20 – 30 years ago and show signs that significant change has taken place since their construction. It is well understood that the effects of exposure to many environmental factors will change the engineering properties of these types of covers relative to their design properties. More specifically, the effects of soil desiccation,freezing, thawing, and animal and plant intrusion are known to deteriorate compacted clay covers over time. While significant research has been performed to observe how hydraulic conductivity may be affected by these environmental factors, very little research has been conducted to evaluate similar effects on Rn diffusivity. The main focus of this study is to assess the Rn flux limiting performance of Rn barriers at four UMTRCA disposal sites after two to three decades of service. Fieldwork was performed in 2016 at the Falls City, TX and Bluewater, NM sites and in 2017 at the Shirley Basin South, WY and Lakeview, OR sites. Rn flux measurements were obtained at each of the four sites from the surface of the Rn barrier at multiple test pit locations. Rn flux measurements were obtained using accumulation chamber methods and continuous alpha Rn detectors, which provide a near real-time concentration buildup curve at intervals specified by the user. Small activated carbon (AC) canisters were used in tandem with the continuous monitors. Test pits were excavated at various locations so that the effects of vegetation, seasonal ponding, animal burrowing, cover protection type/thickness, and Rn barrier thickness could be isolated. In general, greater Rn fluxes were measured at locations where deep-rooting vegetation was found relative to locations without vegetation. Additionally, Rn flux was found to be lower where the Rn barrier remained at levels of water content and saturation near as-built conditions. Rn fluxes measured in 2016 and 2017 were also compared with flux measurements taken immediately after construction of the Rn barrier at three of the sites. The fluxes measured in 2016 and 2017 were found to be greater than those measured immediately after construction at two sites and were relatively unchanged at one site. The barriers at the two sites that showed increases in Rn flux were found to be drier than as-built conditions, which is believed to significantly contribute to the observed increase in Rn flux. Similar magnitudes of Rn flux were measured from the Shirley Basin South site relative to flux measurements taken immediately after construction. The water content and saturation levels of the Rn barrier at this site were found to have increased slightly compared to as-built measurements. A laboratory apparatus was assembled and used to test the Rn diffusion coefficient of thin-walled, 70 mm diameter soil samples taken from the Shirley Basin South, WY site. Rn diffusion coefficients measured with the apparatus were in good agreement with values found in literature. The two methods of Rn flux measurement (continuous monitor and AC canister) were compared to assess the viability of each for flux measurement. The findings show that the two methods were in good agreement when considering the measurement of Rn concentration only. The AC canister method was found to lack reliability and consistency for determining flux when used with accumulation chambers due to the nonlinear concentration buildup of Rn in accumulation chambers and the lack of consistency in the multiple factors that affect this trend.
Keywords: diffusion; flux; tailings; uranium; landfill; radon